2017
DOI: 10.21608/zvjz.2017.29249
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Effect of Pomegranate Juice in Silver Nanoparticles Induced Hepatotoxicity in Mature Male Albino Mice

Abstract: Nano-silvers (AgNPs) are widely used in medical and consumer products thanks to their excellent antimicrobial and anti-carcinogenic effects. Sixty mature male albino mice were randomly distributed into six groups (ten per group). The first group was kept as negative control, the 2 nd one was injected with silver nanoparticles 78 mg/kg BW I/P for 14 days, group 3 was given pomegranate (20 ml/kg BW) orally for 28 days, in the fourth group pomegranate was administrated for 14 days, followed by AgNPs for another 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…In another study, standardized G. biloba extract to 24% ginkgo flavonoids improved oxidative damage in the brain of rats treated with AgNPs, as well as significantly regulated proinflammatory cytokine gene expression in brain tissue [117]. Pomegranate [123] and beetroot [5] juices also provided significant hepatoprotective activities against AgNP-induced toxicity in animal experiments. Albrahim and Alonazi [5] showed that beetroot juice posttreatment has the potential to regulate apoptotic proteins p53 and Bcl-2 in liver tissue of rats treated with AgNPs.…”
Section: Plant-basedmentioning
confidence: 99%
“…In another study, standardized G. biloba extract to 24% ginkgo flavonoids improved oxidative damage in the brain of rats treated with AgNPs, as well as significantly regulated proinflammatory cytokine gene expression in brain tissue [117]. Pomegranate [123] and beetroot [5] juices also provided significant hepatoprotective activities against AgNP-induced toxicity in animal experiments. Albrahim and Alonazi [5] showed that beetroot juice posttreatment has the potential to regulate apoptotic proteins p53 and Bcl-2 in liver tissue of rats treated with AgNPs.…”
Section: Plant-basedmentioning
confidence: 99%
“…Intraperitoneal administration of 33 nm AgNPs at a dose of 78 mg/kg to mice during the period of 14 days resulted in the pronounced increase in the ALT (+126.6%) and AST (+53.5%) levels, while the histological inspection of the liver revealed vascular hyperemia as well as parenchymatous and perivascular aggregations of mononuclear cells [ 33 ]. Another 30-day study where rats were injected intraperitoneally three times a week with 54.9 nm AgNPs revealed a severe hepatotoxic effect.…”
Section: Introductionmentioning
confidence: 99%